1998
DOI: 10.1017/s0025315400039977
|View full text |Cite
|
Sign up to set email alerts
|

Revision of Desmodora With Descriptions of New Desmodorids (Nematoda) from Hydrothermal Vents of the Pacific

Abstract: In this article four species of Desmodoridae, Desmodora alberti sp. nov., Desmodora marci sp. nov., Desmodorella balteata sp. nov. and Desmodorella spineacaudata sp. nov. (Nematoda: Desmodoridae), are described from hydrothermal vents of the Pacific. The genus Desmodora is revised and lists of valid species are provided; four subgenera are reinstated as genera; Xenodesmodora is regarded as genus inquirendum. Definitions of some morphological structures are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 10 publications
2
41
0
Order By: Relevance
“…This species was transferred to Bolbolaimus (erratum?) by Muthumbi et al (1995), but later transferred to Bolbonema by Verschelde et al (1998). Because this species clearly has a head capsule and cephalic setae located posterior to the amphids, we confirm that it belongs to Bolbonema.…”
Section: Remarkssupporting
confidence: 74%
See 1 more Smart Citation
“…This species was transferred to Bolbolaimus (erratum?) by Muthumbi et al (1995), but later transferred to Bolbonema by Verschelde et al (1998). Because this species clearly has a head capsule and cephalic setae located posterior to the amphids, we confirm that it belongs to Bolbonema.…”
Section: Remarkssupporting
confidence: 74%
“…6C), and (3) annulations are present dorsally and ventrally at least to mid-level of amphids, with one continuous annulation anterior to the amphid (see Figs 6B, 7A-C). The genus Bolbonema, however, is characterized by a globular head capsule (i.e., conspicuously thicker cuticle and absence of annulations; Verschelde & Vincx 1996;Verschelde et al 1998). Muthumbi et al (1995) provided an emended diagnosis for Chromaspirina and, more recently, Silva et al (2009) provided an emended diagnosis for Spirinia.…”
Section: Remarksmentioning
confidence: 99%
“…Some species of Desmodora were described from hydrothermal vents of the Pacific (Verschelde et al, 1998). Bernhard et al (2000 reported the presence of the ectosymbiont-harbouring Desmodora masira in the oxygen minimum zone of the Santa Barbara Basin (California margin, 475-600 m).…”
Section: Giant Pockmark Complex Regabmentioning
confidence: 99%
“…Additional individuals were recorded from the marine reaches of the Swan River Estuary, also in similar sediments. Verschelde et al (1998) ascribe two other species to the genus Bolbonema, namely B. brevicolle Cobb, 1920, andB. longisetosum Jensen, 1985.…”
Section: Habitatmentioning
confidence: 99%